Konsekuensi Hukum Pekerja Migran Bawah Umur : Sosialisasi Abdimas Menyikapi Tagar #KaburKeLuar Negeri di SMA Ihsaniyah Kota Tegal - Kanti Rahayu; Kus Rizkianto; Mukhidin Mukhidin; Selviany Selviany; Nuridin Nuridin (BADAN PENERBIT STIEPARI PRESS, 2025)
Migrant workers are a simple term that may be familiar to students and students at Ihsaniyah High School in Tegal City. However, their understanding of the necessary preparation and legal risks that can threaten safety when working abroad, especially if they are illegal migrant workers and minors, are still very limited. In today's social reality, Indonesia's young generation is faced with various structural challenges, such as fierce competition in the world of work, high rates of educated unemployment, inequality in access to education and health, and declining trust in political stability and law enforcement. This condition triggers some of them to look for job opportunities abroad, which are considered more promising in terms of income and better life opportunities. Unfortunately, many of them do not understand the legal consequences and safety risks of working illegally abroad. Therefore, this community service activity (abdimas) is carried out with the aim of providing comprehensive information and repeated education to students. This socialization discusses official regulations related to migrant workers, legal procedures for working abroad, and legal threats to illegal migrant workers. Activity methods include lectures, discussions, and interactive counseling designed to help students understand the dangers and risks of being an illegal migrant worker, including the possibility of becoming a victim or even a perpetrator of a criminal act. The results of the activity showed that students' understanding of the threat of criminal sanctions, legal protection, and the importance of preparing skills and official documents before working abroad has significantly increased. With this activity, it is hoped that students will be wiser in planning for the future, including choosing a career path that is safe, legal, and in accordance with applicable regulations.